ACHIEVEMENT OF TARGET BLOOD PRESSURE LEVEL IN PATIENTS WITH ARTERIAL HYPERTENSION OF 2-3 DEGREE WITH FIXED COMBINATION OF ENALAPRIL OR LOSARTAN WITH HYDROCHLOROTHIAZIDE - A. A. Kudryavtsev; A. S. Ryazanov; N. N. Eremenko; S. A. Kireev (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To compare the effects of fixed combinations of angiotensin converting enzyme inhibitor (enalapril) or angiotensin II receptor antagonist (losartan) with diuretic (hydrochlorothiazide, HCT) on the "office" blood pressure (BP) level in patients with arterial hypertension (HT) of 2-3 degrees.Materials and methods. Patients (n=73; 34 men and 39 women; aged 50.5±5.8) with HT of 2-3 degrees were included in the study. Patients were randomized into 2 groups: patients of group 1 (n=34) received a fixed combination of enalapril with HCT; patients (n=39) of group 2 — a fixed combination of losartan with HCT. The study duration was 24 weeks. "Office" BP levels (Korotkov method) were evaluated.Results. Combination of losartan with HCT shown more prominent effect on systolic BP (reduction from 176.1±2.77 to 122.3±1.54 mm Hg) in comparison with combination enalapril with HCT (reduction from 172.4±1.62 to 129.8±3.4 mm Hg) after 12 weeks of treatment (p<0.05). High frequency of target BP level achievement was observed in patients of groups 1 and 2 (83% and 86% respectively).Conclusion. The fixed combination of enalapril or lozartan with HCT has high efficacy and can be recommended as initial therapy in patients with HT of 2-3 degree.